2016
DOI: 10.1016/j.ijrobp.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Association of Locoregional Control With High Body Mass Index in Women Undergoing Breast Conservation Therapy for Early-Stage Breast Cancer

Abstract: Purpose Obesity, as measured by body mass index (BMI), is a risk factor for distant recurrence and decreased survival in breast cancer. We sought to determine whether BMI correlated with local recurrence and reduced survival in a cohort of predominantly obese women treated with breast conservation therapy. Methods and Materials From 1998–2010, 154 women with early stage invasive breast cancer and 39 patients with ductal carcinoma in situ (DCIS) underwent prone whole breast irradiation. Cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…The association between obesity and cancer recurrence has been widely investigated in breast cancer, and was shown to be associated with local recurrence, distant metastasis, and decreased overall survival [202122]. One possible reason for these findings is that increased adipose tissue may elevate the levels of circulating estrogens, insulin, and insulin-like growth factors, which can facilitate cancer cell growth [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between obesity and cancer recurrence has been widely investigated in breast cancer, and was shown to be associated with local recurrence, distant metastasis, and decreased overall survival [202122]. One possible reason for these findings is that increased adipose tissue may elevate the levels of circulating estrogens, insulin, and insulin-like growth factors, which can facilitate cancer cell growth [22].…”
Section: Discussionmentioning
confidence: 99%
“…The association between obesity and cancer recurrence has been widely investigated in breast cancer, and was shown to be associated with local recurrence, distant metastasis, and decreased overall survival [202122]. One possible reason for these findings is that increased adipose tissue may elevate the levels of circulating estrogens, insulin, and insulin-like growth factors, which can facilitate cancer cell growth [22]. In contrast, some studies have reported that obesity was associated with better prognosis after chemoradiation in other types of cancers, such as cervical cancer, lymphoma, and head and neck cancers [2324252627].…”
Section: Discussionmentioning
confidence: 99%
“…Following BCS, patients receive radiation therapy to the breast and, depending on their stage, may receive regional nodal radiation as well. While some series identify comparable local control rates in obese and normal-weight women undergoing lumpectomy and radiation therapy, others suggest that local recurrence is significantly higher in obese patients [ 18 , 19 •, 20 ]. What is clearer is that the cosmetic outcome with breast conservation (lumpectomy and radiation) may not be as good in obese women compared to normal-weight women.…”
Section: Surgerymentioning
confidence: 99%
“…Hence, most deaths resulting from breast cancer are due to an inability to effectively prevent tumor recurrence [10]. Similarly to epidemiological data linking obesity with increased primary breast cancer risk, obesity is also associated with a greater risk of breast cancer recurrence [1116] (HRs ranging from 1.17 to 1.46 [1315]), as well as a 30–40% increased risk of breast cancer-related death [11, 15, 17, 18]. Because the prevalence of obesity among U.S. women is > 40% [19] and may be even higher among breast cancer survivors [20], understanding the biological underpinnings of the association between obesity and recurrence risk is a critical unmet need.…”
Section: Introductionmentioning
confidence: 99%